REPORT OF THE INTERNATIONAL ASSOCIATION OF FIRE CHIEFS THE AD HOC COMMITTEE ON FIRE - SAFE CIGARETTES (Tufts Archival Research Center, 2007)
Report on fire safety in regard to cigarettes. Cites mattresses and sheets as the most common igniter of fires from cigarettes. Lists various statistics for deaths related to cigarettes. Suggests that several tests would have to be done in order to gauge the toxic effects a fire safe cigarette could potentially have.